1999
DOI: 10.1046/j.1365-2672.1999.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lactoferrin feeding and injection against systemic staphylococcal infections in mice

Abstract: R .S . B H IM AN I , Y . V E ND RO V AN D P . FU RM A NS KI . 1999. Human and bovine lactoferrins (Lfs) and bovine lactoferrin hydrolysate (LH) were assessed in vitro and in vivo for their antibacterial effects on Staphylococcus aureus. Lactoferrins showed weak in vitro antibacterial activity while Fe-saturated Lfs and LH showed no activity. Lactoferrin-treated mice (1 mg, i.v.) when injected i.v. with 10 6 staphylococci, showed 30-50% reduction in kidney infections, and viable bacterial counts in the kidneys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…LF has a number of biological functions, including antimicrobial and immunomodulatory effects in vitro and in vivo (Brock, 1995;Tomita et al, 2002;Vorland, 1999). It has been reported that orally administered bovine LF reduces the number of pathogenic organisms not only in the gastrointestinal tract (Teraguchi et al, 1995;Wada et al, 1999) but also in tissues distant from the gastrointestinal tract in several animal models of infection (Abe et al, 2000;Bhimani et al, 1999;Haversen et al, 2000) and in humans with chronic hepatitis C and tinea pedis (Ishii et al, 2003;Iwasa et al, 2002;Yamauchi et al, 2000). It is known that LF and an LF-derived antimicrobial peptide, lactoferricin B (LFcin B), inhibit in vitro growth of fungi such as Candida albicans (Kuipers et al, 1999;Wakabayashi et al, 1996Wakabayashi et al, , 1998 and Trichophyton mentagrophytes ; it has been shown that orally administered LF shows a host-protective effect against systemic C. albicans infection in mice (Abe et al, 2000) and cutaneous T. mentagrophytes infection in guinea pigs .…”
Section: Introductionmentioning
confidence: 99%
“…LF has a number of biological functions, including antimicrobial and immunomodulatory effects in vitro and in vivo (Brock, 1995;Tomita et al, 2002;Vorland, 1999). It has been reported that orally administered bovine LF reduces the number of pathogenic organisms not only in the gastrointestinal tract (Teraguchi et al, 1995;Wada et al, 1999) but also in tissues distant from the gastrointestinal tract in several animal models of infection (Abe et al, 2000;Bhimani et al, 1999;Haversen et al, 2000) and in humans with chronic hepatitis C and tinea pedis (Ishii et al, 2003;Iwasa et al, 2002;Yamauchi et al, 2000). It is known that LF and an LF-derived antimicrobial peptide, lactoferricin B (LFcin B), inhibit in vitro growth of fungi such as Candida albicans (Kuipers et al, 1999;Wakabayashi et al, 1996Wakabayashi et al, , 1998 and Trichophyton mentagrophytes ; it has been shown that orally administered LF shows a host-protective effect against systemic C. albicans infection in mice (Abe et al, 2000) and cutaneous T. mentagrophytes infection in guinea pigs .…”
Section: Introductionmentioning
confidence: 99%
“…It is thought to play an important role in host defence because it exhibits a variety of biological activities, including antimicrobial activity and immunomodulatory effects, as shown by in-vitro studies [1,2]. It is increasingly appreciated that oral administration of LF or its fragment peptides improves the survival rate and enhances elimination of pathogens from the body of animals or human patients infected with bacteria, fungi, protozoa or viruses [3][4][5][6][7]. Recent studies showed that feeding bovine LF enhances the elimination of pathogens and the rate of symptomatic cure in guinea-pigs and man with dermatophytosis, a very common fungal infection on the skin [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…LF has broad spectrum antimicrobial activity with bacteriostatic activity against Escherichia coli, Klebsiella pneumoniae, Streptococcus mutans and Candida albicans [22]. LF and LFcin are effective against bacteria, fungi, and viruses (Table 3, Figure 1) [3].…”
Section: Function and Spectrummentioning
confidence: 99%